Quantitative Analyse des Hypoxie-induzierbaren Faktors in glatten Muskelzellen und Fibroblasten der Pulmonalarterie und Aorta - Pies, Volker Ulrich; Justus Liebig University Giessen (My University, 2010)
Zielsetzung der Arbeit war die vergleichende quantitative Analyse der Induktion des Hypoxie-induzierbaren Faktors (HIF) an pulmonalarteriellenund aortalen Gefäßzellen, welche aus Kaninchen isoliert wurden. Zu diesem Zweck wurde ein Reportergen-Assay-Verfahren etabliert.Es wurden Plasmide konstruiert, bei denen das Hypoxie-responsive Element (HRE), das die HIF-abhängige Geninduktion der Zielgene steuert, an verschiedene konstitutive Promotoren gekoppelt wurde, die ein Luciferase-Reportergen kontrollieren. Diese Plasmide wurden zur Transfektion der vaskulären Versuchszellen verwendet.

The aim of the study was the comparative quantitative analysis of the induction of hypoxia-inducible factor (HIF) to pulmonary artery and aortic vascular cells, which were isolated from rabbits. For this purpose, a reporter gene assay method was established.Plasmids were constructed in which the hypoxia-responsive element (HRE), which controls the HIF-dependent gene induction of target genes, had been linked to different constitutive promoters,which control a luciferase reporter gene. These plasmids were used for transfection of the vascular cells.
Quantitative analysis of hypoxia-inducible factor in smooth muscle cells and fibroblasts of the pulmonary artery and aorta
Keywords: HIF; Hypoxie; Remodeling; glatte Muskelzelle; Fibroblast; HIF; hypoxia; remodeling; smooth muscle cell; fibroblast; ddc:610